Mental concepts: theoretical, observational or dispositional approach? - Pokropski, Marek (Hybris, 2017)
In the article I discuss the conceptual problem of other minds and different approaches to mental concepts. Firstly, I introduce the conceptual problem and argue that solutions proposed by theory-theory and direct perception approach are inadequate. I claim that mental concepts are neither theoretical terms nor observational terms. Then, I consider third option which states that mental concepts are dispositional terms, i.e. they concern particular patterns (stereotypes) of behavior. Finally, I argue that dispositional approach is to some extent coherent with phenomenological account and that phenomenological concept of embodiment can improve this position.